ANALISIS KEPUASAN PENGGUNA TRANSPORTASI UMUM JAK LINGKO DI JAKARTA SELATAN - Denny Supriyadi, (2020)
This research is a quantitative study aimed at knowing the influence of price, service quality, and promotion to the satisfaction of public transport users Jak Lingko in South Jakarta. The population in this research is a user who has used Jak Lingko more than once, aged 15 to 50 years, with activities in South Jakarta, male and female. Sample size is taken as much as 75 respondents, with non probablity sampling methods and sampling purposive. Data collection is done through the dissemination questionnaire. Analysis techniques used are analysis methods PLS (Partial Least Square) with Smart software PLS 3.0. The results of this study indicate that (1) the price has no significant effect on user satisfaction with a line coefficient value of 0.184. (2) Service quality has significant effect on user satisfaction with line coefficient value of 0.308. (3) The promotion has significant effect on user satisfaction with a line coefficient value of 0.408. R Square Value on user satisfaction of 0,617.